Does a large loss of bank capital cause ever-greening or flight to quality? Evidence from Japan - Wako Watanabe (Osaka University, Institute of Social and Economic Research (ISER), 2004)
Constructing a strong and unique instrument for bank capital from the empirical observation of Japanese banks' past behavioral changes, we identify the impact of capital adequacy on the allocation of bank lending supply across low quality and high quality borrowers. We find that, in FY 1997, a large loss of capital resulting from the regulator's tougher stance against banks induced banks to rebalance their lending portfolio toward low quality borrowers. Our findings also suggest that the public recapitalization of banks in FY 1998 effectively helped banks abandon the assistance of such zombies.
Keywords: C21; G21; 330; ever-greening; flight to quality; bank capital; instrumental variable; Kreditgeschäft; Kreditrisiko; Kreditwürdigkeit; Bankenregulierung; Geldpolitische Transmission; Instrumentalvariablen-Schätzmethode; Japan